The comparison of solar-powered hydrogen closed-cycle system capacities for selected locations - Solomin, E.; Selvanathan, S.P.; Kumarasamy, S.; Kovalyov, A.; Maddappa Srinivasa, R. (MDPI AG, 2021)
The exhaustion of fossil fuels causes decarbonized industries to be powered by renewable energy sources and, owing to their intermittent nature, it is important to devise an efficient energy storage method. To make them more sustainable, a storage system is required. Modern electricity storage systems are based on different types of chemical batteries, electromechanical devices, and hydrogen power plants. However, the parameters of power plant components vary from one geographical location to another. The idea of the present research is to compare the composition of a solar-powered hydrogen processing closed-cycle power plant among the selected geographical locations (Russia, India, and Australia), assuming the same power consumption conditions, but different insolation conditions, and thus the hydrogen equipment capacity accordingly. The number of solar modules in an array is different, thus the required hydrogen tank capacity is also different. The comparison of equipment requires building an uninterrupted power supply for the selected geographical locations, which shows that the capacity of the equipment components would be significantly different. These numbers may serve as the base for further economic calculations of energy cost.